2017
DOI: 10.1371/journal.pone.0177979
|View full text |Cite
|
Sign up to set email alerts
|

Changes in hospitalizations for chronic respiratory diseases after two successive smoking bans in Spain

Abstract: Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 41 publications
(65 reference statements)
0
24
1
1
Order By: Relevance
“…After removal of duplicates, 12 392 unique citations were screened by title and abstract, and 65 full texts were sourced. Of these, 41 EPOC studies 16 , 17 , 18 , 19 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 and three non-EPOC studies 65 , 66 , 67 fit the inclusion criteria ( figure 1 ; appendix, pp 6, 7 ). The EPOC studies included data from more than 57 million births, and from 4·6 million GP diagnoses and 2·7 million hospital admissions for respiratory conditions.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After removal of duplicates, 12 392 unique citations were screened by title and abstract, and 65 full texts were sourced. Of these, 41 EPOC studies 16 , 17 , 18 , 19 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 and three non-EPOC studies 65 , 66 , 67 fit the inclusion criteria ( figure 1 ; appendix, pp 6, 7 ). The EPOC studies included data from more than 57 million births, and from 4·6 million GP diagnoses and 2·7 million hospital admissions for respiratory conditions.…”
Section: Resultsmentioning
confidence: 99%
“…The appendix (pp 8–20) details the main characteristics of the EPOC studies. Among these, 26 were interrupted time series studies, 16 , 17 , 18 , 19 , 31 , 32 , 37 , 38 , 40 , 42 , 43 , 45 , 46 , 48 , 50 , 51 , 52 , 54 , 55 , 57 , 58 , 59 , 61 , 62 , 63 , 64 14 were controlled interrupted time series studies, 28 , 29 , 33 , 34 , 35 , 36 , 39 , 41 , 44 , 47 , 49 , 53 , 56 , 60 and one had a regression discontinuity design, 30 a quasi-experimental design bearing close resemblance to interrupted time series methodology. 68 The three non-EPOC studies were uncontrolled before-and-after studies ( appendix, p 21 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased EDA in winter months can be explained by the quantity of elderly population in our time series composed of different characteristics in terms of time, place and person. In the admissions regarding to RD, behavioral risk factor such as smoking [22], besides higher vehicle emissions in the cities, often and synchronously ascending amount of pollutants in the atmosphere, meteorological parameters, and exposed allergens were reported to be the reasons of increased emergency department admissions due to asthma and respiratory allergies specifically for the atopic individuals [4,20]. Rosychuk et al demonstrated that in Canada, the asthma-based admissions are expected to increase in spring months [23] and COPD admissions are expected to rise much more in winter and autumn period [17].…”
Section: Discussionmentioning
confidence: 99%
“…The implementation of public smoking bans and clean air policies has led to a reduction in the hospitalization for asthma, and these policies should be reinforced in as many countries as possible . School‐specific targeted intervention work is ongoing …”
Section: Framing the Issuementioning
confidence: 99%